Curriculum and Pandemic: Time of Crisis and Opportunity for Disruption - Díaz-Barriga-Arceo, Frida (2020)
The virtual homeschooling strategy is discussed in terms of prevailing inequality and the transmissive approach adopted. Likewise, it talks about some paths of disruptive innovation in the field of the school curriculum.